2000
DOI: 10.1021/ja000784g
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Control of Superparamagnetic Properties of Magnesium and Cobalt Spinel Ferrite Nanoparticles through Atomic Level Magnetic Couplings

Abstract: A correlation between the electron spin-orbital angular momentum coupling and the superparamagnetic properties has been established in MgFe 2 O 4 and CoFe 2 O 4 spinel ferrite nanoparticles. The contribution to the magnetic anisotropy from the Fe 3+ lattice sites is almost the same in both nanocrystallites as neutron diffraction studies have shown a similar cation distribution in these two types of spinel ferrite nanoparticles. Due to the strong magnetic couplings from Co 2+ lattice sites, the blocking tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
208
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(237 citation statements)
references
References 28 publications
22
208
1
Order By: Relevance
“…Gopal reddy et al reported the response of copper ferrite (CuFe2O4) and zinc ferrite (ZnFe2O4) for hydrogen sulfide (H2S) and that of nickel ferrite (NiFe2O4) for chlorine gas (Cl2) [10]. One of the present authors (Y-L.Liu) was confirmed that ZnFe2O4 gas sensor has sensing properties for H2S gas [11].Magnesium ferrite (MgFe2O4) is one of the important ferrites with spinel structure [13]. It is used as a catalyst [14] and humidity sensor [15].…”
Section: Introductionsupporting
confidence: 54%
“…Gopal reddy et al reported the response of copper ferrite (CuFe2O4) and zinc ferrite (ZnFe2O4) for hydrogen sulfide (H2S) and that of nickel ferrite (NiFe2O4) for chlorine gas (Cl2) [10]. One of the present authors (Y-L.Liu) was confirmed that ZnFe2O4 gas sensor has sensing properties for H2S gas [11].Magnesium ferrite (MgFe2O4) is one of the important ferrites with spinel structure [13]. It is used as a catalyst [14] and humidity sensor [15].…”
Section: Introductionsupporting
confidence: 54%
“…As the crystallite size of sample S1 annealed at 800°C is about 48 nm and the distribution of cations over the interstitial sites is almost an inverse spinel, it appears that annealing at 800°C, sample S1 might have changed from nanocrystalline form to bulk form. The above observation suggests that at relatively low annealing temperature, the thermal energy is low to overcome the energy barrier to an ordered (stable) cation distribution [11,32]. As the annealing temperature is increased, there is a redistribution of cation between the tetrahedral and octahedral sites in order to relax the strain at the lattice site.…”
Section: Structural Analysismentioning
confidence: 99%
“…For very high temperatures, applicable materials will naturally be limited to refractory materials with good heat resistance, like borides [6][7][8] and oxides [9][10][11][12], etc. The material system of spinel-type oxide exists for a wide range of constituent elements, and various chemical and physical properties have been studied [13][14][15][16][17]. Our initial motivation to focus particularly on the spinel-type magnesium ferrites is because its magnetic properties have been extensively studied [13,14], and we are interested in the link between magnetism (magnetic semiconductors) and thermoelectric properties due to our previous work in chalcopyrite, where thermoelectric enhancement was indicated [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The material system of spinel-type oxide exists for a wide range of constituent elements, and various chemical and physical properties have been studied [13][14][15][16][17]. Our initial motivation to focus particularly on the spinel-type magnesium ferrites is because its magnetic properties have been extensively studied [13,14], and we are interested in the link between magnetism (magnetic semiconductors) and thermoelectric properties due to our previous work in chalcopyrite, where thermoelectric enhancement was indicated [18][19][20]. It is also a system where the crystal structure is well-characterized in a wide temperature range, and a system with good thermal stability and sintering characteristics, and in the present work we tried to learn more about processing effects on its thermoelectric properties.…”
Section: Introductionmentioning
confidence: 99%